Developing 21(st )century accreditation standards for teaching hospitals: the Taiwan experience - Huang, Chung-I (BioMed Central, 2009)
BACKGROUND: The purpose of this study is to establish teaching hospital accreditation standards anew with the hope that Taiwan's teaching hospitals can live up to the expectations of our society and ensure quality teaching. METHODS: The development process lasted two years, 2005-2006, and was separated into three stages. The first stage centered on leadership meetings and consensus building, the second on drafting the new standards with expert focus groups, and the third on a pilot study and subsequent revision. RESULTS: Our new teaching hospital accreditation standards have six categories and 95 standards as follows: educational resources (20 items), teaching and training plans and outcomes (42 items), research and results (9 items), development of clinical faculty and continuing education (8 items), academic exchanges and community education (8 items), and administration (8 items). CONCLUSIONS: The new standards have proven feasible and posed reasonable challenges in the pilot study. We hope the new standards will strengthen teaching and research, and improve the quality of hospital services at the same time.